Integrating the Values of Moderate Islam in Social Science Learning: A Qualitaive Study at Islamic Junior High School (MTs) Darul A’mal Metro - Jusmirah Jusmirah (Journal of Research in Islamic Education, 2020)
The purpose of the article describing social studies learning integrated with moderate Islamic ideology is able to ward off religious ideology (theology) with characteristics: First, escapist radicalism, trying to release worldly life, ascetic life, freeing themselves from worldly pleasures that are considered poisonous and virtual. Second, theological-ideological radicalism, building an exclusive community, as an anti-group identity the surrounding world that is considered to be like the devil's world must be eradicated. The method of data collection is done by observation and interviews obtained from the staff of 8 MTs educators and 4 students who were analyzed using a quantitative approach. From the stages of the research conducted found several main components in counteracting radical ideology through the integration of social studies learning namely 1). Formulating competency achievements, 2). Formulating the description of the subjects in the lesson plan based on moderate Islamic values, 3). Implementing learning by instilling an attitude ( tassamuh, tawasud, tawazun ). Conclusion of the changes made, first through the achievement of competence, secondly formulating a description of each social studies subject integrated with the Islamic concept of Rahmatan lil 'alamin , thirdly learning strategies are integrated with the concept of wasaton, fourth in evaluating the portion of the attitude assessment component. The resulting impact: 1). Islam rahmatan lil 'alamin , build tolerance, harmony, and peace without violence. 2). Islam will continue to synergize with culture, in search of the relevance of universal values ​​of religion in responding to life's problems.